The Effect of Intensive Training Using Load on Some Physical Abilities in Deaf Futsal Players - Khadem, Ali; Shamel, Wameed (Journal of Physical Education, 2020)
The research aimed at designing a training program according to intensive training in deaf futsal players as well as identifying the effect of this program with a load on some physical abilities in deaf futsal players. The researcher used the descriptive method on (16) players. The main experiment was applied using an intensive training program to collect the data that was treated using proper statistical operations to conclude significant differences between pre and posttests in all physical abilities. In addition to that, the researchers concluded the effect of an intensive training program on the subjects under study. Using the program designed by the researcher on futsal players. The researchers recommended making similar studies on other physical and skill abilities as well as other sports.